Effects of group problem solving activities on active learners’ performance in online learning / Norazlina Ahmad … [et al.] - Ahmad, Norazlina; Tasir, Zaidatun; Kassim, Mohd Mamsin Anor; Zainal Abidin, Zainal Azhar (UiTM Press, 2016)
Online learning is one of the 21st century teaching methods but researchers and practitioners face problems in applying appropriate teaching strategies to improve learners’performance. Previous studies have shown that matching learners’ learning styles with appropriate teaching methods present great potential in making online learning easier and more effective as well as enhancing learners’ performance. Based on that promising finding, this study aims to investigate the effects of matching teaching strategies using the group problem solving approach with active learning styles to gauge learners’ achievement. The Felder and Silverman Learning Style Model and Group Problem Solving were used in this study to investigate the effects of teaching strategies on active learners’ performance. Twenty-one learners enrolled in the Multimedia Interactive Application course were used as study samples. The instruments used were learners’ log data, performance test results and learning activities in Moodle based LMS. The results showed that online learning utilizing the group problem solving approach on active learners improved their performance.